Financial stability of Islamic banks: a review of the literature - Odeduntan, Akeem Kolawole; Adewale, Abideen Adeyemi (European Research Centre for Islamic Finance, University of Turin, Italy, 2015)

(untitled)
The recent global financial crisis that began in the US and spread sporadically to other parts of the world has been a sort of awakening that financial stability of financial institutions should be on check from time to time. This scenario has called for a concerted effort that may possibly be geared towards introducing a framework or policy that tends to promote and sustain economic growth and stability. The present paper therefore reviews financial stability of banks by surveying the extant literature on the subject. It employs library method to gather information and further analyze it by way of comparative, inductive and deductive methods. The paper establishes that while some Islamic banks are relatively stable in terms of their financial activities, some banks are not.